Process, System and Styles of Savings Culture in Banthadindang-og Community, Phatthalung Province - Dhammasaccakarn, Wanchai; Ratchapolsit, Atsawaluk; Dhammasajjakan, Angkana; Hanghon, Pornpichet (Area Based Development Research Journal, 2019)
The objectives of this research are to study the processes, systems and styles of savings culture for children and youth of one community in Pabon district, Phatthalung province. Data are collected by interviews (informal, semi-structured and in-depth) and observations from 23 key informants who are community leaders, community master plan staff, villagers, and children and youth leaders, who have participated in the activity. Content analysis is then conducted and results are presented in descriptive format. The findings of the Part I - saving process - reveal 4 steps: 1) raising awareness by parents and family; 2) saving practice, depending on individuals’ context, such as children learning on savings from the school and religious doctrine; 3) expansion of savings in multi-dimensional activities, such as planting trees and animal husbandry; and 4) knowledge transfer, such as sharing knowledge with friends. Part II: saving culture systems refer to the three major domains. Firstly, social institution, such as family, temple, school, plays an important role in disseminating knowledge and nurturing a complete human being. Secondly, knowledge and wisdom is a valuable asset when living in a community; for stance, knowledge on plantation and animal farming. Thirdly, transfer of knowledge and wisdom is important as a communication process among community members in order to recognize the value of saving; for example, by demonstrating, storytelling and training. Part III: saving culture styles, consists of 5 styles. The first style is through animal husbandry such as raising cow, pigs, chickens, and catfish. The second style is agricultural savings such as farming, rubber plantation, and eclectic gardening. The third style is by possessing real estate and valuable objects savings, such as land, gold, amulets and ancient objects. The fourth style is intellectual savings such as attending meetings, training courses, study visits, and reading. The fifth style involves monetary savings, such as collecting coins and banknotes in a piggy bank, playing share, and promise money savings. For further promotion of saving behavior, the knowledge and findings from the study will be disseminated to the community.